Preliminary result fot the Rb-Sr mineral isochron ages of granitic rocks from Cape Omega and Oku-iwa Rock, Prince Olav Coast, East Antarctica - Nishi, Naoko; Kawano, Yoshinobu; Kagami, Hiroo (National Institute of Polar Research, 1999)
P(論文) The granitic rocks of the Cape Omega, and Oku-iwa Rock, yield the age of 439.0±12.3 Ma with an initial Sr isotope ratio of 0.70609±0.00014 and 417.9±2.2 Ma with an initial Sr isotope ratio of 0.70646+0.00002, respectively. These ages represent the time when these granitic rocks cooled down to the closure temperature of biotite and are consistent with previous reported K-Ar biotite ages (339-449 Ma) of granitic rocks in the Liitzow-Holm Complex. Calculated cooling rates of the Cape Omega and the Oku-iwa Rock areas are 5.3-4.1°C/Ma and 3.8-3.6°C/Ma, respectively. These results are consistent with cooling rates for the amphibolite facies terrain of the Liitzow-Holm Complex previously reported. departmental bulletin paper